SOURCES AND MECHANISMS OF UNIVERSAL POSTAL SERVICE FUNDING (Perner's Contacts, 2013)
Presented paper searches optimal way of universal postal service ensuring in Czech republic. At first it is necessary to define appropriate extent and structure of universal service regarding specifics of particular state (including decision of postal network future form). In second step, there is a necessity to assess exact level of USO net costs by appropriate method and just after that to decide the way of its additional funding if necessary. Generally recommended way of USO additional funding by compensation fund or state budget application is not convenient solution. More appropriate method is special type of mechanism so called “ pay or play“ preventing cherry-picking and based on such principle, that each provider of up to now reserved services, who will want to provide these services in strictly defined the most lucrative state areas, will be obligated to provide these services on the whole state territory. Naturally, he will have possibility to use access to universal service provider network guaranteed by direction 2008/6/EC.